Moving beyond numerals: a meta-analysis of research methods and theoretical application in media gatekeeping studies (2011)
This study investigates trends in media gatekeeping research, specifically in terms of research methods and theoretical application. Through a meta-analysis, 128 media gatekeeping-related studies purposively drawn from communication-based journals (published between 2000 and 2008) were content analysed. The findings reveal a progressive drift from quantitative method (38.3%) towards qualitative method (57.0%): a deviation from previous submissions that communication researchers prefer quantitative method to qualitative approach (Berg, 2001; Abawi, 2008). However, results confirm the previous findings that majority of communication studies are not theory-driven (Kim and Weaver, 2002) as only 44(34.4%) of the articles examined had theoretical frameworks. The study encourages more theoretical applications and synthesis of methods in media gatekeeping research.